2020
DOI: 10.1177/1847980420935718
|View full text |Cite
|
Sign up to set email alerts
|

Wideband absorber based on conductive ink frequency selective surface with polarization insensitivity and wide-incident-angle stability

Abstract: In this article, a wideband, polarization-insensitive, and wide-incident-angle stable absorber based on conductive ink frequency selective surface is presented. The presented absorber is compatible with screen printing technology. The design and absorption principle of the proposed absorber is presented, and simulation analysis is conducted. The simulation results show that in the frequency range 6.58–16.38 GHz, the absorptivity of the proposed absorber is greater than 90%, while the relative absorption bandwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 30 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Figures 5(e)-5(f) show electric field distribution of FSS layer at two resonance frequencies, i.e., 13.91 GHz and 37.63 GHz, it can be observed that the electric fields are mainly concentrated on the fringe of FSS layer, so the resonance is closely related to the side length of FSS layer. [22] It is well known that a resistive film is usually printed on the upper surface of the PI layer in traditional method, but resistive film on the top of an MMA may be cracked or mismatched when the PVC-PI-PTFE-metal plate structure is conformal to a curved surface. To avoid surface abrasion of the resistive film and to improve absorbing performance when the MMA is curved, as a development, resistive film is arranged on the lower surface of the PI herein, this is the most difference between this work and existed researches.…”
Section: Resultsmentioning
confidence: 99%
“…Figures 5(e)-5(f) show electric field distribution of FSS layer at two resonance frequencies, i.e., 13.91 GHz and 37.63 GHz, it can be observed that the electric fields are mainly concentrated on the fringe of FSS layer, so the resonance is closely related to the side length of FSS layer. [22] It is well known that a resistive film is usually printed on the upper surface of the PI layer in traditional method, but resistive film on the top of an MMA may be cracked or mismatched when the PVC-PI-PTFE-metal plate structure is conformal to a curved surface. To avoid surface abrasion of the resistive film and to improve absorbing performance when the MMA is curved, as a development, resistive film is arranged on the lower surface of the PI herein, this is the most difference between this work and existed researches.…”
Section: Resultsmentioning
confidence: 99%
“…4 Due to the superior characteristics, frequency-selective absorbers (FSAs) have received more attention. 5 Unlike conventional absorbers, FSA not only has one or more absorption bands but also has a passband [6][7][8][9] or stopband. [10][11][12][13] FSA with passbands can provide low insertion loss transmission and out-of-band wave absorption.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, FSSs based on indium tin oxide (ITO) have been extensively studied due to their easy fabrication. ,, The use of these ITO-based FSSs for wideband EM wave absorption has been experimentally demonstrated. Another widely investigated resistive FSS is based on conductive ink, in which the FSS patterns are formed directly by inkjet printing using cheap ink.…”
Section: Introductionmentioning
confidence: 99%